Vitis vinifera leaf extract protects against glutamate-induced oxidative toxicity in HT22 hippocampal neuronal cells and increases stress resistance properties in caenorhabditis elegans - Duangjan, Chatrawee; Rangsinth, Panthakarn; Zhang, Shaoxiong; Gu, Xiaojie; Wink, Michael; Tencomnao, Tewin (Frontiers in nutrition, 2021)
Vitis vinifea has been used for traditional medicines, food, beverages, and dietary antioxidant supplements. The chemical compositions and biological activities of the fruits and seeds have been extensively investigated. However, the biological effects of the leaves are limited, and its anti-neurodegeneration or antiaging activities are little known. The current work aims to study the beneficial effects of V. vinifera leaf extract on neuroprotective effects in HT22 cells, antiaging, and oxidative stress resistance properties in the Caenorhabditis elegans model. The ethanol extract was characterized by phytochemical composition using gas/liquid chromatography-mass spectrometry and reversed-phase high-performance liquid chromatography. The beneficial effects of V. vinifera ethanol (VVE) extract on antioxidant properties, neuroprotective effects, and the underlying mechanisms were studied by in vitro and in vivo studies. In HT22 cells, we found that VVE has a protective effect against glutamate-mediated oxidative stress-induced cell death. The gene expression of cellular antioxidant enzymes such as CAT, SODs, GSTs, and GPx was upregulated by VVE treatment. Moreover, VVE was also shown to alleviate oxidative stress and attenuate reactive oxygen species accumulation in C. elegans. We demonstrated that VVE could upregulate the expression of stress-response genes gst-4 and sod-3 and downregulate the expression of hsp-16.2. Our results suggest that the oxidative stress resistance properties of VVE are possibly involved in DAF-16/FoxO transcription factors. VVE reduced age-related markers (lipofuscin) while did not extend the life span of C. elegans under normal conditions. This study reports the neuroprotective effect and antioxidant activity of V. vinifera leaf extract and suggests its potential as a dietary or alternative supplement to defend against oxidative stress and age-related diseases.